Democracy, lobbying and economics - Milan Žák (Review of Economic Perspectives, 2019)
The paper deals with the issue of lobbying, defined as a democratic means of promoting interests. The text tries to find answers to the problems in the current economic theory. The basic links are defined by using a simple graphic model, which are further examined by the SWOT analysis. The result is the knowledge that the basic coordination mechanism is the market - the information market. The role of government lies above all in creating a favourable institutional environment that does not interfere with spontaneous market relations. However, there are certain situations that the government could or should regulate. These situations are described by three hypothetical scenarios - a society without lobbying, a society where lobbing exists, but it is not transparent, and a society where lobbing is transparent, leading to a final discussion of possible directions and ways of its regulation.
Keywords: A11; A12; C70; D72; D82; 330; Impact of Lobbying on Democracy; Public Choice; New Institutional Economy; New Political Economy